Fatigue performance of asphalt binders modified with varying nanomaterials - Al-Hamdou, Ali M.; Albayati, Amjad H. (Results in engineering, 2025)
•Exploring the effect of five nanomaterials (NA, NS, NT, NZ, CNT) on the fatigue resistance of asphalt binders.•Nanomaterials were incorporated at varying dosages (2−10 % for NA, NS, NT; 1−5 % for NZ, CNT) to optimize binder performance.•Comprehensive testing included physical, rheological, and fatigue performance evaluations.•The optimal performance was achieved at 6 % for NA and NT, 2 % for NS and CNT, and 1 % for NZ.•Results highlight the potential of nanomaterials to enhance the long-term durability of asphalt binders. This study investigates the influence of five nanomaterials nano-alumina (NA), nano-silica (NS), nano-titanium (NT), nano-zinc oxide (NZ), and carbon nanotubes (CNT)on enhancing the fatigue resistance of asphalt binders. NA, NS, and NT were incorporated at dosages of 2 %, 4 %, 6 %, 8 %, and 10 %, while NZ and CNT were added at 1 %, 2 %, 3 %, 4 %, and 5 %. A series of physical, rheological, and performance-based tests were conducted, including penetration, softening point, ductility, and rotational viscosity. Based on the outcomes of the overall desirability evaluation, the first three dosages of each nanomaterial were selected for further testing due to their superior workability and binder flexibility. Subsequent investigations included the high-temperature performance grade, fatigue parameter (G*.sin δ), Linear Amplitude Sweep (LAS), and IDEAL-CT test integrated with Digital Image Correlation (DIC). The results confirmed that nanomaterial modification significantly enhanced asphalt binder performance, though the effectiveness varied with type and dosage. Physical tests demonstrated improved stiffness, softening point, and reduced temperature susceptibility, with slight ductility losses at higher dosages. Rotational viscosity analysis indicated that low-to-moderate contents ensured workability excluding high CNT dosages which exceeded Superpave limits. High-temperature PG improved notably with NS, NZ, and CNT, while NA and NT showed limited gains. Fatigue parameter results (G*.sin δ) identified NA and NT as the most consistent in reducing cracking susceptibility. LAS testing confirmed superior fatigue lives at optimal dosages of 6 % NA, 6 % NT, 2 % NS, 2 % CNT, and 1 % NZ, while higher concentrations often caused agglomeration and performance decline. IDEAL-CT and DIC analyses validated these findings by demonstrating increased fracture energy, CT index, and more uniform strain distributions in nano-modified mixtures compared to neat asphalt. FTIR spectra confirmed reduced oxidative aging most prominently with NT and NA while SEM revealed enhanced microstructural cohesion and reduced surface defects. The integration of the Overall Desirability (OD) framework confirmed NT-6 as the most effective dosage, followed by NZ-1 and NS-2, while higher dosages often led to poor compatibility and performance decline. Complementary cost–effectiveness analysis further demonstrated that lower dosages of NZ, NT, and NS achieved the best balance between technical performance and economic viability, whereas excessive CNT and NT contents were not recommended due to unfavorable cost-to-performance ratios. These findings highlight that dosage optimization is critical for translating nanomaterial benefits into practical pavement engineering applications, ensuring enhanced durability with rational investment of resources.